The Development of PAHIT (Papan Hitung) Teaching Aids in Mathematics Learning for Grade II Elementary School Students - Ratnawati; Suci Rahma Putri; Armi Marlina (The Future of Education Journal, 2025)
This research is motivated by problems encountered in the implementation of mathematics learning in Grade II, such as low student interest, weak understanding, and difficulties in grasping mathematical concepts, particularly in the topic of addition. An effort to address these issues is by developing the PAHIT (Papan Hitung) teaching aid, which aims to improve student learning outcomes through engaging and interactive media. The purpose of this study is to produce a valid, practical, and effective PAHIT (Papan Hitung) teaching aid for teaching mathematics to Grade II students at SDN 07 Koto Baru. This research uses the Research and Development (R&D) method. The development model applied is ADDIE, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The data collected includes both qualitative and quantitative types. Instruments used in the study include observation sheets, interview guidelines, validity instruments, practicality instruments, and effectiveness instruments. Data collection techniques involved interviews, observations, and questionnaires. The analysis focused on the validity, practicality, and effectiveness of the teaching aid. The results of the research and development produced a PAHIT (Papan Hitung) teaching aid for the mathematics topic of addition in Grade II at SDN 07 Koto Baru. Based on assessments from three validators, the tool achieved an average score of 0.79, categorized as valid and therefore suitable for classroom use. The practicality of the PAHIT teaching aid was rated by students with an average percentage of 97.5% (very practical), and by teachers with a 100% rating (very practical). The effectiveness of the teaching aid was also high, with an average score of 90%, categorized as effective.